Pengaruh ROA, EPS, Dan DER Terhadap Return Saham (Pada Perusahaan Sektor Healthcare Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2021) - Delpania Delpania; Yun Fitriano; Nenden Restu Hidayah (UNIVED Press, 2023)
This study aims to determine the effect of Return On Assets (ROA), Earnings per Share (EPS), and Debt to Equity Ratio (DER) on Stock Returns in Healthcare Sector companies listed on the Indonesia Stock Exchange in the 2017-2021 period, either partially or partially. simultaneous. This company focuses on Healthcare sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2021. Based on the sampling criteria, the research sample obtained is 12 companies with a total of 25 observations using purposive sampling method. This research is quantitative descriptive. Based on its function, this study aims to analyze data on companies in the Healthcare sector. The data used is descriptive statistical analysis test, followed by classical assumption test including normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, and the statistical method used to analyze the data using multiple linear regression analysis. The data in this study are secondary data with a time per year for 5 years starting from 2017-2021 obtained from the Indonesia Stock Exchange (IDX). The results showed that the best company, namely the company PT. Indofarma Tbk (INAF) with an average score of 153.69. While the results of multiple linear regression analysis to determine the effect of ROA, EPS, and DER on Stock Returns show that partially ROA has a positive effect on Stock Return, with a value of tcount 3.650 > ttable 2.003. EPS has a positive effect on stock returns, with a tcount of 2,623 > ttable of 2,003. DER has a positive effect on Stock Return with a tcount value of 5.820 > ttable 2003. Simultaneously ROA, EPS, and DER together have a positive effect on Stock Return with Fcount 32,266 > Ftable 2.76..